The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1093/oxfordjournals.aje.a115157
|View full text |Cite
|
Sign up to set email alerts
|

Serum Triglycerides as an Independent Risk Factor for Death From Coronary Heart Disease in Mtddle-Aged Norwegian Men

Abstract: The relation between nonfasting serum triglycerides and death from coronary heart disease was studied in 37,546 men aged 35-49 years who were examined during 1972-1977 in four counties in Norway. During an average follow-up period of nine years, 369 deaths from coronary heart disease occurred. In univariate analysis, log(triglycerides) were a weak, but statistically significant predictor of coronary death in the age groups 40-44 and 45-49 years. Within-area analysis showed that a high triglyceride area represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…Several large observational studies have assessed the association between blood lipid concentrations and cardiovascular risk. It was reported that both higher TG and TC levels were significant independent predictors of coronary death only in participants in the upper age range (Tverdal et al, 1989). After simultaneous adjustment for a variety of coronary risk factors, TG concentrations manifested significant correlation with MI, ischemic heart disease and survival after 26 years of follow-up in a large-scale prospective cohort study (Nordestgaard et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Several large observational studies have assessed the association between blood lipid concentrations and cardiovascular risk. It was reported that both higher TG and TC levels were significant independent predictors of coronary death only in participants in the upper age range (Tverdal et al, 1989). After simultaneous adjustment for a variety of coronary risk factors, TG concentrations manifested significant correlation with MI, ischemic heart disease and survival after 26 years of follow-up in a large-scale prospective cohort study (Nordestgaard et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The previous study on men also included the Oslo study and the Troms0 study (1974), in which only men were studied. 6 A detailed description of the study procedures has been given by Bjartveit et al7 All people participating answered a questionnaire at home about history of cardiovascular disease, diabetes, treatment for hypertension, symptoms of angina pectoris, physical activity during leisure, smoking habits, and stress factors in social life. In this study the healthy group consists of those who gave negative answers to questions about myocardial infarction, angina pectoris, other heart disease, atherosclerosis of legs, cerebral stroke, diabetes, treatment for hypertension, use of nitroglycerine, and symptoms suggesting angina pectoris or atherosclerosis obliterans, or both.…”
Section: Methodsmentioning
confidence: 99%
“…From these studies we have previously reported non-fasting triglyceride concentration to be a weak predictor of death from coronary heart disease in men; the strength of association depending heavily on whether total cholesterol concentration was accounted for. 6 The period of follow up is now sufficient (12 to 16 years) to give fairly precise estimates of the relation between triglyceride concentration and mortality from coronary disease in women.…”
Section: Introductionmentioning
confidence: 99%
“…We collapsed current and former smokers to ever-smokers. We further categorized ever-smokers according to the following factors: age at smoking initiation (16,(17)(18)(19)(20)(21)(22)(23)(24), 25 years), numbers of cigarettes smoked per day (1-9, [10][11][12][13][14][15][16][17][18][19]20), smoking duration in years (1-19, 20-29, 30-39, 40), and number of pack-years (i.e., number of cigarettes smoked per day, divided by 20, multiplied by the duration of smoking in years; 0-9, 10-19, 20). All subjects not being current or former smokers were classified as never smokers.…”
Section: Exposure Informationmentioning
confidence: 99%